The Influence Of Perceived Usefulness, Ease Of Use, And Risk On The Interest In Using Qris Services With Attitude Toward Using As An Intervening Variable - Ade Syafitri; Marliyah Marliyah; Tuti Anggraini (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study aims to determine the influence of the perception of usefulness, ease of use and risk on interest in using qris services with attitude toward using as an intervening variable. This study is quantitative research using the SPSS Statistics program with a sample of 98 respondents using QRIS services. The data analysis technique used is multiple linear regression. By using probability sampling techniques. The results of this study show that the perception of usefulness has an effect on interest in using QRIS services, the perception of ease of use has a positive and significant effect, while the perception of risk does not have a significant effect on interest in using QRIS services. The perception of usefulness does not have a significant effect on attitude toward using, the perception of ease of use has a negative effect, the perception of risk has a negative effect while interest in using QRIS services has a positive effect on attitude toward using. Based on the path analysis, the attitude toward using variable cannot be used as an intervening variable between the perception of the usefulness of ease of use and the risk to interest in using QRIS services and attitude toward using can be used as an intervening variable for the variable interest in using QRIS services. Keywords: Usefulness; Ease; Risk; QRIS; Interest; Attitude Toward Using